Emerging outbreaks associated with conflict and failing healthcare systems in the Middle East. (13th August 2018) - Raad, Issam I.; Chaftari, Anne-Marie; Dib, Rita Wilson; Graviss, Edward A.; Hachem, Ray
Abstract: The escalating conflicts in the Middle East have been associated with the rapid collapse of the existing healthcare systems in affected countries. As millions of refugees flee their countries, they become vulnerable and exposed to communicable diseases that easily grow into epidemic crises. Here, we describe infectious disease epidemics that have been associated with conflicts in the Middle East, including cholera, poliomyelitis, measles, cutaneous leishmaniasis, and diphtheria, that call for appropriate preventive measures. Local ongoing wars and failing healthcare systems have resulted in regional and global health threats that warrant international medical interventions.